Aptamer-Drug Conjugates of Active Metabolites of Nucleoside Analogs and Cytotoxic Agents Inhibit Pancreatic Tumor Cell Growth - Yoon,S; Huang,K-W; Reebye,V; Spalding,D; Przytycka,TM; Wang,Y; Swiderski,P; Li,L; Armstrong,B; Reccia,I; Zacharoulis,D; Dimas,K; et al. (MOLECULAR THERAPY-NUCLEIC ACIDS, 2016)
Aptamer-drug conjugates (ApDCs) have the potential to improve the therapeutic index of traditional chemotherapeutic agents due to their ability to deliver cytotoxic drugs specifically to cancer cells while sparing normal cells. This study reports on the conjugation of cytotoxic drugs to an aptamer previously described by our group, the pancreatic cancer RNA aptamer P19. To this end, P19 was incorporated with gemcitabine and 5-fluorouracil (5-FU), or conjugated to monomethyl auristatin E (MMAE) and derivative of maytansine 1 (DM1). The ApDCs P19-dFdCMP and P19-5FdUMP were shown to induce the phosphorylation of histone H2AX on Ser139 (γ-H2AX) and significantly inhibited cell proliferation by 51%–53% in PANC-1 and by 54%–34% in the gemcitabine-resistant pancreatic cancer cell line AsPC-1 (p ≤ 0.0001). P19-MMAE and P19-DM1 caused mitotic G2/M phase arrest and inhibited cell proliferation by up to 56% in a dose-dependent manner when compared to the control group (p ≤ 0.001). In addition, the cytotoxicity of P19-MMAE and P19-DM1 in normal cells and the control human breast cancer cell line MCF7 was minimal. These results suggest that this approach may be useful in decreasing cytotoxic side effects in non-tumoral tissue.